Driving Factors The Buddhist Community’s Intention to Boycott Israeli-Affiliated Products in Indonesia - Saifudin Saifudin; Dyah Kusumawati; Sepia Hartiningsih (Jurnal Administrasi Bisnis)
The spirit of caring for fellow humans is a lantern whose light can penetrate ethnic, racial, national and religious boundaries. This research is motivated by the war between Israel and Palestine. This paper's goal is to identify the variables that affect of the willingness of Buddhists to boycott Israeli-affiliated products. This paper investigates the influence of subjective norms, positive anticipated emotions and product judgment on the boycott of Israeli-affiliated products. The data sample used in this research was 142 respondents from 17 provinces in Indonesia. Samples are taken using purposive sampling, namely taking samples with certain conditions. To analyze survey data and interpret research results, Partial Least Squares Structural Equation Modeling (PLS-SEM) was used for the model that was created. This test aims to compare the direct and indirect effects the relationship between the dependent and independent variables. The test results show the favorable and strong impact of subjective norms on the willingness to boycott. Positive anticipated emotions also have a positive and significant effect on willingness to boycott. However, product judgment does not affect willingness to boycott.